Performance-based functional evaluation of non-operative and operative treatment after anterior cruciate ligament injury - Moksnes, H.; Risberg, M. A. (Scandinavian Journal of Medicine & Science in Sports, 2009)
Highly active anterior cruciate ligament (ACL)-injured patients are usually recommended surgical treatment as the primary intervention. The objective of this study was to compare the functional outcome in a cohort of individuals after non-operative treatment to individuals after surgical treatment at a 1-year follow-up. One hundred and twenty-five subjects with a mean age of 27.2 years (±8.6 years), and participating in level I or II activities were included. Baseline and 1-year follow-up examination included four single-legged hop tests, IKDC 2000, KOS-ADLS, KT-1000 knee arthrometer measurement, VAS, episodes of giving way, and activity level. Fifty-one percent went through non-operative treatment. Non-operated subjects performed significantly better on two of the four single-legged hop tests compared with the ACL-reconstructed subjects at the 1-year follow-up. No other differences were observed. Both groups performed an average >90% compared with their uninjured leg on all single-legged hop tests at the 1-year follow-up. The IKCD 2000 scores in the non-operated and ACL-reconstructed group were on average 86 and 87. ACL-injured subjects should be informed of the possibility of success after non-operative treatment, but future studies are needed to determine significant predictive factors for success for non-operative and surgically treated individuals.